Die Geheimnisse der oberen und der unteren Welt : Magie im Islam zwischen Glaube und Wissenschaft - Günther, Sebastian; Pielow, Dorothee Anna Maria (Islamic History and Civilization, 2018)
Die Geheimnisse der oberen und der unteren Welt ( The Secrets of the Upper and the Lower World ) is a substantial new collection of essays on magic in Islamic cultural history. Both comprehensive and innovative in its approach, this book offers fresh insights into an important yet still understudied area of Islamic intellectual history. The seventeen chapters deal with key aspects of Islamic magic, including its historical developments, geographical variants, and modern-day practices. The general introduction identifies and problematizes numerous sub-topics and key practitioners/theoreticians in the Arabo-Islamic context. This, along with terminological and bibliographical appendices, makes the volume an unparalleled reference work for both specialists and a broader readership. Contributors: Ursula Bsees, Johann Christoph Bürgel, Susanne Enderwitz, Hans Daiber; Sebastian Günther, Mahmoud Haggag, Maher Jarrar, Anke Joisten-Pruschke, Fabian Käs, Ulrich Marzolph, Christian Mauder, Tobias Nünlist, Khanna Omarkhali, Eva Orthmann, Bernd-Christian Otto, Dorothee Pielow, Lutz Richter-Bernburg, Johanna Schott andamp; Johannes Thomann.